'Land yes, dam no!' Justice-seeking strategies by the anti-dam movement in the Ribeira Valley, Brazil. Issue 2 (23rd February 2018) - Thorkildsen, Kjersti
Abstract : This contribution examines how and with what effects the Movement of People Threatened by Dams (MOAB) in the Ribeira Valley, Brazil, works at various scales simultaneously. It is argued that MOAB was kicked off by mobilising Afro-descendants around livelihood issues, and that one of the first anti-dam strategies was to claim quilombola recognition and land rights at the state level. MOAB soon expanded its network and broadened its agenda to include procedural justice, targeting federal and international agencies for recourse. The paper concludes that MOAB has successfully used different scales for framing, mobilisation and action, which has contributed to the dam project being put on hold for almost three decades.